Analysis of spatial variability of turmeric (Curcuma longa L. syn. C. domestica Val.) yield in India - Govindaswamy, P Subbian, N Sankaran, K Kandiannan, K K Chandaragiri, M (Journal of Spices and Aromatic Crops, 2002)
This paper examines the yield variability of turmeric in India. The data on maximum, minimum and mean fresh rhizome yield of 200 experiments from secondary sources of published research papers/reports were collected. These data were utilized with an objective to calculate summary statistics and to identify maximum and minimuln yields and yield differences obtained in each state. The summary statistics indicated that in India maximum yield ranged between 4.59 and 95.0 t ha-1 with a mean of 28.48 ± 14.29 t ha-1. The Ininimum yield ranged between 1.34 and 56.25 t ha-1 with a mean of 13.73 ± 18.60 t ha-1 and the mean yield ranged from 3.09 to 72.68 t ha-1 with a mean of 22.99 ±11.60 t ha-1. The maximum yield obtained in all the cases was due to adoption of improved produCtion techniques such as variety, manure and better crop management practices compared to minhnum yield of control treatment. The yield differences between maximum and minimum ranged from 6.69 to 93.50 t ha-1.